Sulfasalazine could modulate the CD44v9‐xCT system and enhance cisplatin‐induced cytotoxic effects in metastatic bladder cancer. Issue 4 (1st March 2019) - Ogihara, Koichiro; Kikuchi, Eiji; Okazaki, Shogo; Hagiwara, Masayuki; Takeda, Toshikazu; Matsumoto, Kazuhiro; Kosaka, Takeo; Mikami, Shuji; Saya, Hideyuki; Oya, Mototsugu
Abstract : The prognostic role of CD44v9, a variant isoform of CD44 and a new cell surface marker of cancer stem cells, remains unclear in bladder cancer (BC) patients. Furthermore, limited information is available on the functional role of sulfasalazine (SSZ), which could modulate the CD44v9‐xCT system in order to enhance cisplatin (CDDP)‐induced cytotoxicity and inhibit the metastatic potential of BC. CD44v9 protein expression was examined immunohistochemically in 63 muscle invasive BC (MIBC) patients who underwent radical cystectomy. CD44v9 expression was independently associated with disease recurrence and cancer‐specific death in MIBC. Cytotoxic effects, glutathione levels, and reactive oxygen species production by SSZ and CD44v9 and phospho‐p38 MAPK protein expression by SSZ with or without CDDP were assessed in MBT‐2V cells with highly metastatic potential. Sulfasalazine exerted cytotoxic effects against MBT‐2V cells by inhibiting glutathione levels and inducing the production of reactive oxygen species. Sulfasalazine in combination with CDDP appeared to exert strong cytotoxic effects against MBT‐2V cells by inhibiting CD44v9 expression and upregulating phospho‐p38 MAPK expression. The inhibitory effects of SSZ with or without CDDP were also investigated using an MBT‐2V lung metastatic model. In the murine lung metastatic BC model, SSZ significantly prolonged animal survival. Furthermore, the combination of SSZ with CDDP exerted stronger inhibitory effects on the establishment of lung tumor nodules than SSZ or CDDP alone. CD44v9 expression could be a clinical biomarker for predicting poor outcomes in MIBC patients. Sulfasalazine in combination with CDDP has potential as a novel therapy against metastatic BC. Abstract : This is the first report to show the therapeutic effects of not only sulfasalazine (SSZ), but also the combination of SSZ and cisplatin (CDDP) in a metastatic bladder cancer model, suggesting the potential of SSZ and CDDP combination therapy for metastatic bladder cancer.